Advancements in minimally invasive surgery for adolescent idiopathic scoliosis: A case series and literature review - Yi-Jen Ho; Wen-Chun Chiang; Ying-Chao Lin (Tzu Chi Medical Journal)
Objectives: Minimally invasive surgery (MIS) has emerged as a promising alternative to conventional open techniques in the management of adolescent idiopathic scoliosis (AIS). Materials and Methods: This study presents a case series of six patients who underwent MIS for AIS at a spine center, employing a synergistic blend of intraoperative fluoroscopy, cone-beam computed tomography scans, and three-dimensional navigation technology. The surgical procedures were meticulously guided, with a focus on ensuring safety and precision in posterior pedicle fixation. Results: Our findings demonstrate substantial correction of spinal curvature postoperatively, with a mean Cobb’s angle reduction of 51.75%. In addition, MIS facilitated a mean estimated blood loss of 241.67 ml and a mean surgical duration of 391.33 min. Conclusion: Comparison with conventional open techniques reveals comparable or superior outcomes in terms of correction rates, patient recovery, and opioid usage. This study underscores the potential of MIS in achieving favorable clinical outcomes while minimizing surgical impact and advancing the treatment landscape for AIS.